Short chain fatty acids: the messengers from down below - Mansuy-Aubert, Virginie; Ravussin, Yann (Frontiers in Neuroscience, 2023)
Short-chain fatty acids (SCFAs), produced by the metabolism of dietary fibers in the gut, have wide-ranging effects locally and throughout the body. They modulate the enteric and central nervous systems, benefit anti-inflammatory pathways, and serve as energy sources. Recent research reveals SCFAs as crucial communicators between the gut and brain, forming the gut-brain axis. This perspective highlights key findings and discusses signaling mechanisms connecting SCFAs to the brain. By shedding light on this link, the perspective aims to inspire innovative research in this rapidly developing field.